Counseling of the Bogor Police Binmas Sat in Preventing Criminal Actions of Theft by Increasing (Indonesian Journal of Police Studies, 2024)
Indonesia as a state of law, based on the 1945 Constitution of the Republic of Indonesia article 1 paragraph 3. Explained in Law number 2 of 2002 concerning the Indonesian National Police that the task of the National Police is as a tool of the state with the role of realizing domestic security. The tasks of the National Police are also classified as the main task of maintaining security and public order, providing protection, protection and services as well as maintaining domestic security. The conventional crime is still dominating Bogor district and has increased over the past three years. In order to realize the seven programs of Kapolri, Sat Binmas Polres Bogor as the foremost fortress of pre-eminent and preventive will carry out their tasks optimally. In analyzing, the author used several theories and concepts such as management theory, role theory, legal system theory, the concept of polmas, the concept of prevention, the concepts of a thief with weights. Qualitative approach is analytical descriptive that used to obtain the broadest picture of the problems that occur. Qualitative approach provides descriptive data consist of words orally delivered by primary sources at the time of the interview, so that the problem can be explored in depth. The results obtained in this study fount that: (1) The description of a criminal act of theft by weighting at Bogor Police Station; (2) The implementation of counseling in the field that is still lacking in terms of personnel ability and less precisely target; (3) The influencing factors are internal and external. Internal factors such as human resources, budget, facilities, infrastructure and leader policies. External factors such as community participation, cooperation and social communication. From the results obtain in this research, the author suggests Bhabinkamtibmas to use media to communicate like Whatsapp groups. The conclusion for Kapolres Bogor is to add police officers, join the Binmas vocational education, procure two-wheeled motorized vehicles and consider the policy of the leadership.
Keywords: Binmas; pencegahan